2019
DOI: 10.3233/jad-181144
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidogenic Nanoplaques in Blood Serum of Patients with Alzheimer’s Disease Revealed by Time-Resolved Thioflavin T Fluorescence Intensity Fluctuation Analysis

Abstract: Background: Biomarkers are central to current research on molecular mechanisms underlying Alzheimer’s disease (AD). Their further development is of paramount importance for understanding pathophysiological processes that eventually lead to disease onset. Biomarkers are also crucial for early disease detection, before clinical manifestation, and for development of new disease modifying therapies. Objective: The overall aim of this work is to develop a minimally invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 64 publications
(48 reference statements)
0
31
1
Order By: Relevance
“…Thus, ultrasensitive analytical methods are needed to improve the accuracy of blood-based biomarkers for early-stage AD prediction. Recently, Tiiman et al (2019) identified the Aβ aggregates in blood serum from AD patients and found a higher concentration and larger size of ThT-reactive amyloidogenic nanoplaque compared to healthy controls through the SM FCS-ThT method. This result demonstrated the feasibility of detecting the actual amyloid states in the blood that corresponds to the fibrils in the brain.…”
Section: Application Of Smts For Amyloidosis Diagnosismentioning
confidence: 99%
“…Thus, ultrasensitive analytical methods are needed to improve the accuracy of blood-based biomarkers for early-stage AD prediction. Recently, Tiiman et al (2019) identified the Aβ aggregates in blood serum from AD patients and found a higher concentration and larger size of ThT-reactive amyloidogenic nanoplaque compared to healthy controls through the SM FCS-ThT method. This result demonstrated the feasibility of detecting the actual amyloid states in the blood that corresponds to the fibrils in the brain.…”
Section: Application Of Smts For Amyloidosis Diagnosismentioning
confidence: 99%
“…A possible diagnosis tool for AD has been the use of positron emission tomography (PET) with radiotracers to detect the presence of fibrillar deposits of amyloid in the brain that are greater than 1 mm in size. PET scans are quite expensive and there are issues in correlating deposits of amyloid with progression of AD, as its been found that plaques also deposit in the brains of healthy individual [107]. Detecting A␤ via antibodies in serum and cerebrospinal fluid (CSF) have also shown to be promising biomarkers but the predicative power of these biomarkers has not been particularly encouraging [108,109].…”
Section: Biomarkers Of Admentioning
confidence: 99%
“…Detecting A␤ via antibodies in serum and cerebrospinal fluid (CSF) have also shown to be promising biomarkers but the predicative power of these biomarkers has not been particularly encouraging [108,109]. Furthermore, attempts to correlate serum/CSF with PET are not very convincing as of yet [107]. A potential minimally invasive variant to measuring amyloid without the use of expensive radiotracers or immunebased probes was developed by Tiiman et al [107].…”
Section: Biomarkers Of Admentioning
confidence: 99%
See 2 more Smart Citations